2015
DOI: 10.1155/2015/727530
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Dexmedetomidine Provides Superior Patient Comfort and Tolerance Compared to Intravenous Midazolam in Patients Undergoing Flexible Bronchoscopy

Abstract: Dexmedetomidine, an α 2 agonist, has demonstrated its effectiveness as a sedative during awake intubation, but its utility in fiberoptic bronchoscopy (FOB) is not clear. We evaluated the effects of midazolam and dexmedetomidine on patient's response to FOB. The patients received either midazolam, 0.02 mg/kg (group M, n = 27), or dexmedetomidine, 1 µg/kg (group D, n = 27). A composite score of five different parameters and a numerical rating scale (NRS) for pain intensity and distress were used to assess patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 27 publications
0
37
1
1
Order By: Relevance
“…In our trial, the incidence of total children movements of 3 groups was 46.81% 22/47 versus 34.88% 15/43 versus 17.78% 8/45, respectively, of DR1, DR2, DR3, which is higher than previous studies reported. [9] However, only a small number of children required to convert to propofol (25.53% 12/47 vs 13.95% 6/43 vs 4.65% 2/45, respectively, of DR1, DR2, DR3). The reason may be mainly due to the different combinations of drugs among these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our trial, the incidence of total children movements of 3 groups was 46.81% 22/47 versus 34.88% 15/43 versus 17.78% 8/45, respectively, of DR1, DR2, DR3, which is higher than previous studies reported. [9] However, only a small number of children required to convert to propofol (25.53% 12/47 vs 13.95% 6/43 vs 4.65% 2/45, respectively, of DR1, DR2, DR3). The reason may be mainly due to the different combinations of drugs among these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Midazolam, propofol, etomidate, opioids, inhalational agents, or a combination of these drugs have been widely used during flexible bronchoscopy; however, each of these drugs has its limitations. [912] Midazolam, propofol, and etomidate have no analgesic property and sedative pharmacology variability of different patients may be responsible for respiratory depression. Opioids such as fentanyl, sufentanil, and remifentanil can provide excellent analgesia without enough sedation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bronkoskopiden 10 dakika önce uygulanan 1 mg/kg deksmedetomidinin güvenli ve etkin sedasyon sağladığı, 0.02 mg/kg dozda uygulanan midazolam kadar tolere edildiği, daha iyi hasta konforu sağladığı bulunmuştur (23) .…”
Section: Deksmedetomidinunclassified
“…Another study exploring dexmedetomidine administration versus midazolam in patients undergoing flexible bronchoscopy demonstrated superior patient comfort and tolerance in the group receiving the alpha-2 agonist. 32 Oral alpha-2 agonists, such as clonidine, as well as sedating antihistamines such as hydroxyzine could also be considered. IM ketamine is a common agent used in office-based dental anesthesia as well.…”
Section: Alternatives To Benzodiazepinesmentioning
confidence: 99%